When home is where the stress is: expanding the dimensions of housing that influence asthma morbidity. Issue 11 (20th October 2006) - Sandel, M; Wright, R J
Abstract : The influence of physical housing quality on childhood asthma expression, especially the effect of exposure to moulds, allergens, and pollutants, is well documented. However, attempts to explain increasing rates and severity of childhood asthma solely through physical environmental factors have been unsuccessful, and additional exposures may be involved. Increasing evidence has linked psychological stress and negative affective states to asthma expression. At the same time, recent scholarship in the social sciences has focused on understanding how social environments, such as housing, "get under the skin" to influence health, and suggests that psychological factors play a key role. While there is relevant overlapping research in social science, psychology, economics, and health policy in this area, findings from these disciplines have not yet been conceptually integrated into ongoing asthma research. We propose to expand the dimensions of housing considered in future asthma research to include both physical and psychological aspects which may directly and indirectly influence onset and severity of disease expression. This synthesis of overlapping research from a number of disciplines argues for the systematic measure of psychological dimensions of housing and consideration of the interplay between housing stress and physical housing characteristics in relation to childhood asthma.